Conceptual approaches to the interaction of labor market entities and educational institutions in the Russian Federation within the ecosystem based on neural network mechanisms - Elena Eduardovna Alenina; Vera Vitalievna Ziulina; Ilya Aleksandrovich Alenin; Sergey Vladimirovich Bolotnikov; Dmitry Vladimirovich Redin; Lyubov Viktorovna Borodacheva (Revista on line de Política e Gestão Educacional)
The purpose of the study: to develop and describe, the process of functioning of a neural network system of expert justification of management decisions in the field of preparation of educational programs for promising activities using graphical modeling methods. Results: conceptual approaches to ensuring the interaction of labor market entities and educational organizations of the Russian Federation within the information and communication ecosystem based on neural network mechanisms described in the BPMN 2.0 notation have been proposed. The main subjects of the system have been characterized through the "pool" and "swimline" tools, their interaction through the "flow", "messages flows" tools, the main operations displayed through private processes data mining, IDSS, communication driven and document driven interaction. The scientific novelty of the study: the concept of strategic interaction between the subjects of the labor market and educational institutions of the Russian Federation based on automation of communication and the use of neural network mechanisms has been proposed.